Facile Preparative Access to Bioactive Silicon Oxycarbides with Tunable Porosity - Xie, Fangtong (Materials (Basel), 2019)
In the present work, Ca-containing silicon oxycarbides (SiCaOC) with varying Ca content have been synthesized via sol-gel processing and thermal treatment in inert gas atmosphere (pyrolysis). It has been shown that the as-prepared SiCaOC materials with low Ca loadings (Ca/Si molar ratios = 0.05 or 0.12) were X-ray amorphous; their glassy network contains Q(3) sites, indicating the presence of Ca(2+) at non-bridging-oxygen sites. SiCaOC with high Ca content (i.e., Ca/Si molar ratio = 0.50) exhibits the presence of crystalline calcium silicate (mainly pseudowollastonite). Furthermore, it has been shown that the incorporation of Ca into the SiOC glassy network has a significant effect on its porosity and specific surface area. Thus, the as-prepared Ca-free SiOC material is shown to be non-porous and having a specific surface area (SSA) of 22.5 m(2)/g; whereas SiCaOC with Ca/Si molar ratio of 0.05 exhibits mesoporosity and a SSA value of 123.4 m(2)/g. The further increase of Ca content leads to a decrease of the SSA and the generation of macroporosity in SiCaOC; thus, SiCaOC with Ca/Si molar ratio of 0.12 is macroporous and exhibits a SSA value of 39.5 m(2)/g. Bioactivity assessment in simulated body fluid (SBF) confirms the hydroxyapatite formation on all SiCaOC samples after seven days soaking, unlike the relatively inert ternary silicon oxycarbide reference. In particular, SiCaOC with a Ca/Si molar ratio of 0.05 shows an increased apatite forming ability compared to that of SiCaOC with Ca/Si molar ratio of 0.12; this difference is considered to be a direct consequence of the significantly higher SSA of the sample with the Ca/Si ratio of 0.05. The present work indicates two effects of Ca incorporation into the silicon oxycarbide glassy network on its bioactivity: Firstly, Ca(2+) is shown to contribute to the slight depolymerization of the network, which clearly triggers the hydroxyapatite formation (compare the bioactive behavior of SiOC to that of SiCaOC with Ca/Si molar ratio 0.12 upon SBF exposure); secondly, the Ca(2+) incorporation seems to strongly affect the porosity and SSA in the prepared SiCaOC materials. There is an optimum of Ca loading into the silicon oxycarbide glassy network (at a Ca/Si molar ration of 0.05), which provides mesoporosity and reaches maximum SSA, both highly beneficial for the bioactive behavior of the materials. An increase of the Ca loading leads, in addition to the crystallization of calcium silicates, to a coarsening of the pores (i.e., macroporosity) and a significant decrease of the SSA, both negatively affecting the bioactivity.